Neuropeptide F-expressing neurons in Drosophila constitute centrifugal pathway to optic lobes - Jing Wang; Fritz-Olaf Lehmann (PLoS ONE, 2026)
Neuropeptide F (NPF), the Drosophila homolog of mammalian neuropeptide Y (NPY), plays a central role in the integrative regulation of internal states and behavior by modulation of diverse processes such as feeding, sleep, learning, and stress response. In this study, we systematically map the population of NPF-expressing neurons in the adult Drosophila brain using genetic labeling, microscopic imaging, and morphological analysis. Genetic labeling with GFP reveals ~50 NPF-expressing neurons, which can be grouped into five major anatomical clusters. Each cluster exhibits distinct projection patterns targeting different brain regions, suggesting specialized roles in various behavioral domains. Morphometric analysis indicates that NPF neuronal subtypes vary in soma size, soma location and arborization patterns. Besides P1, P2 and L1 neurons, we identify two ventrolateral NPF-expressing neurons per hemisphere. While the somata of ventrolateral neurons reside in the protocerebrum, their neurites project centrifugally to the optic lobes. This anatomy positions ventrolateral neurons as a potential link between the NPF system and previously reported changes in visual attention. Collectively, the data presented here extend the morphological framework of the NPF circuit in Drosophila and may help to understand the principles by which neuromodulators orchestrate brain-wide regulation of behavior.